Development of Marketing Strategy for Waqf Benefits from Takaful and Sharia Insurance Investments in Indonesia (A Case Study of PT Allianz Life Syariah) - fatmawati Hidayat; Achmad Firdaus (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to identify internal and external factors that influence the success of marketing Islamic insurance policy waqf in Indonesia, and to formulate effective marketing strategies to increase sales of this product. The research used is SWOT analysis and brand analysis with a qualitative-descriptive approach, using primary data from interviews and observations as well as secondary data from literature and industry reports. The results of the study show that the main strength of the Islamic insurance policy waqf product lies in the support of strong sharia regulations and the largest Muslim population in the world. However, challenges such as low public literacy about waqf and lack of understanding of marketing personnel about the product are significant weaknesses. Great opportunities are seen from the increasing public interest in productive waqf, while threats include competition with conventional products and low public trust in the insurance industry.